CLASSROOM MANAGEMENT IN IMPROVING THE SOCIAL SKILLS OF ELEMENTARY SCHOOL STUDENTS - Yudiaka, Deki; Wasliman, Iim (LP2M IAI Al-Khairat Pamekasan, 2025)
The background of this study is students' social skills. This study generally aims to evaluate the classroom management applied at SDN Peuteuycondong 1, Cianjur Regency, and its impact on students' social skills. Specifically, to determine the planning, organization, implementation, and supervision of classroom management applied at the school. This study uses a case study approach with qualitative methods. Data were collected through observation, interviews, and documentation studies. The results of this study are that (1) classroom planning is designed by setting clear goals, arranging space and time, and selecting teaching materials that support the development of students' social skills. (2) Effective classroom organization and time allocation support the implementation of social activities such as group discussions and collaborative projects. (3) The implementation of management involves practical activities designed to improve students' social skills, with effective teacher supervision and leadership. (4) Supervision is carried out through monitoring, evaluation, and adjustment of management based on feedback and evaluation results. Consistent supervision helps in monitoring student progress and increasing the effectiveness of management. This study concludes that the classroom management implemented at SDN Peuteuycondong 1 has proven effective in improving students' social skills. However, the success of this management is highly dependent on careful planning, good organization, consistent implementation, and ongoing supervision.